TEKNIK BUDIDAYA IN VITRO Eleutherine sp. (Bawang Sabrang) - Hoesen, Djadja Siti Hazar (Jurnal Teknologi Lingkungan, 2010)
Vegetative propagation from bulb excised of Eleutherine sp. (Iridaceae) were cultured in Murashige and Skoog (MS) medium supplemented with plant growth regulator (PGR) Benzyl adenine (BA) 1 mg/l at initiation stage, BA (2 and 5) mg/l for induced shoot buds formation at multiplication stage. In this study also BA 2 mg/l and BA 2 mg/l combined with naphthalein acetic acid (NAA) 0.5 mg/l were treated for rooting planlets formation. Calli formation were induced with auxin PGR picloram 1 mg/l combined with 2,4 dichlorophenoxy acetic acid (2,4-D) 0.5 and 1 mg/l in concentrations. The media contained 2 mg/l cytokinin (BA) without auxin (NAA), resulted the highest shoot buds formation. Rooting planlets were produced in MS medium combined with BA and NAA.MS medium contains Picloram 1 mg/l and 2,4-D 1 mg/l was optimal for frequency oncalli initiation (100%) and the largest diameter of calli also represented in cultured MS medium with picloram 1 mg/l and 2,4-D 1mg/l. In acclimatization stage, 100% of planlets survived and successfully transplanted to soil medium in the field.Key words: in vitro, Eleutherine sp.